Examining recent effects of caffeine on default mode network and dorsal attention network anticorrelation in youth - Orrin D. Ware; Sarah E. Chang; Wesley K. Thompson; Alexandra S. Potter; Hugh Garavan; Micah E. Johnson; Lucina Q. Uddin (PLoS ONE, 2025)
Objectives In adolescence, caffeinated beverage consumption is negatively associated with cognitive functioning. The default mode network and dorsal attention network are anticorrelated brain systems that are essentially implicated in attention. Despite the importance of the anticorrelation of default mode network – dorsal attention network on cognitive functioning, no studies have examined the association between this anticorrelation and recent caffeine consumption among youths. This study analyzed baseline data from the Adolescent Brain Cognitive Development℠ Study, the largest longitudinal study examining brain development and adolescent health in the United States, to explore the associations between caffeinated beverage consumption and the strength of anticorrelation between the default mode network – dorsal attention network. Methods A total of N = 4,673 early adolescents (average age 9.9 years, standard deviation = 0.6) had self-report data for two caffeine variables: [a] last 24-hour caffeinated beverage consumption (Yes/No) and [b] weekly caffeinated beverage consumption (continuous). A mixed-effects model was fitted with default mode network – dorsal attention network anticorrelation strength as the outcome. Results Most of the baseline ABCD sample did not consume a caffeinated beverage in the last 24 hours (n = 3,910; 83.7%). Controlling for covariates (age, attention problems, BMI, family, head motion, MRI scanner, and sex), neither the caffeinated beverage variables nor their interaction were statistically significant. Conclusions Our study findings identified that approximately 16% of our sample consumed caffeine in the last 24 hours prior to the magnetic resonance imaging scan. We did not find caffeine to impact the default mode network – dorsal attention network anticorrelation strength in this sample. This study may guide the interpretation of functional magnetic resonance imaging results among adolescents who consume caffeinated beverages.